KASTURI TOBACCO LEAF FLAVONOIDS AS BIOACTIVE COMPOUNDS IN PERIODONTAL ANTIBACTERIAL MUCOADHESIVE GEL - QONITA NAFILAH FEBI; MALIHATUL ROSIDAH; DERI ABDUL AZIS; ENDAH PUSPITASARI; ARI SATIA NUGRAHA; BANUN KUSUMAWARDANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The tobacco leaves are a rich source of many biologically active substances. Flavonoids are one of the bioactive substances contained in tobacco leaves with a wide range of pharmacological properties. This study has been aimed to formulate the antibacterial periodontal gel containing the flavonoids fraction of Kasturi tobacco (Nicotiana tabacum) leaves. Methods: Fraction flavonoids obtained from methanolic extracts of tobacco leaves, which have been purified from nicotine. Different concentrations of flavonoids fraction (0, 25, 0,5, 1, 2, and 4 mg/ml) were prepared with Carbopol-974P. The strength of flavonoid gel adhesion in ex vivo mucosa was tested by the falling liquid film method. Evaluation of in vitro antibacterial agent was followed by the disk diffusion method. Results: The flavonoid gels have better adhesion parameters (time, strength, and distance) than gel bases. The antimicrobial by the zone of inhibition studies proved that flavonoids periodontal gels with concentrations of 4 mg/ml are highly active against Porphyromonas gingivalis with the zone of inhibition >10 mm which was higher than quercetin gel formulations (control groups). Conclusion: Gel formulation containing the flavonoids fraction of Kasturi tobacco (N. tabacum) leaves could be a good candidate for periodontal gel with good mucoadhesive gel and antibacterial agent.